PROSEDUR PENGIRIMAN BARANG IMPOR DALAM MENDORONG KEGIATAN INDUSTRI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SUMATERA UTARA - Damanik, Azmi Rahmita (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2024)
This study is based on the premise that an understanding of the settlement procedures of document in order to import expenditures will increase confidence in the business, which in turn can eliminate the high cost in each of the documents and imported goods. It is developed for executives imports to provide a deep understanding of delivery procedures of imported goods and can utilize the facilities and services available. The theory is used to analyze the problems is about understanding the import and industrial activities. This research was conducted at the Department of Industry and Commerce of North Sumatra province. This study uses a case study which is descriptive of a study to collate, classify, interpret and interpret the data so as to provide a description of the problem to be studied. The results obtained and at the conclusion of this study include that with the policies pursued in the government's import activities in Indonesia, then over time, imports will be more towards the target of the objectives of the Indonesian state. Can meet the needs of society, the state revenue will increase because of their income, improve the economy of the people, promoting the growth of the industry, obtaining the goods can not be produced in their own country, expand the market and increase the advantages of modern technology transfer.